2005
DOI: 10.1016/j.neuron.2005.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Activity Regulates Interstitial Fluid Amyloid-β Levels In Vivo

Abstract: Aggregation of the amyloid-beta (Abeta) peptide in the extracellular space of the brain is central to Alzheimer's disease pathogenesis. Abeta aggregation is concentration dependent and brain region specific. Utilizing in vivo microdialysis concurrently with field potential recordings, we demonstrate that Abeta levels in the brain interstitial fluid are dynamically and directly influenced by synaptic activity on a timescale of minutes to hours. Using an acute brain slice model, we show that the rapid effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

58
969
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,122 publications
(1,032 citation statements)
references
References 39 publications
58
969
3
2
Order By: Relevance
“…Confirmation of presynaptic localization of oligomers by electron microscope would be optimal; however, detection of intraneuronal, particularly oligomeric, Ab is limited by the technical difficulty of detecting Ab antigens, which are hydrophobic and difficult to detect by conventional immunocytochemical methods, especially in postmortem tissue. 67 On the basis of previous and current results, we posit that most synaptosomal Ab represents an intraterminal pool largely localized within endosomal and autophagic vesicles, consistent with a strong literature showing synaptic release of Ab 25,68,69 and disruption of autophagy in AD. 69e72 Relatively few examples in the literature have found cellular or pathologic factors associated with cognitive protection in subjects with AD pathology.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Confirmation of presynaptic localization of oligomers by electron microscope would be optimal; however, detection of intraneuronal, particularly oligomeric, Ab is limited by the technical difficulty of detecting Ab antigens, which are hydrophobic and difficult to detect by conventional immunocytochemical methods, especially in postmortem tissue. 67 On the basis of previous and current results, we posit that most synaptosomal Ab represents an intraterminal pool largely localized within endosomal and autophagic vesicles, consistent with a strong literature showing synaptic release of Ab 25,68,69 and disruption of autophagy in AD. 69e72 Relatively few examples in the literature have found cellular or pathologic factors associated with cognitive protection in subjects with AD pathology.…”
Section: Discussionsupporting
confidence: 89%
“…8,18e21 In humans, electron microscopic studies have documented synapse-associated Ab and tau, 22,23 and much work documents activity-dependent release of synaptic Ab into interstitial fluid, which drives local Ab deposition in human subjects and in rodents. 4,24,25 Of importance, most synapse-associated Ab in cortical synapses of AD patients consists of soluble oligomeric species, 26 and synaptic tau pathology in AD also includes accumulations of SDS-stable tau oligomers. 27e31 With the use of synaptosomes (resealed nerve terminals) from the cortex of postmortem human subjects and a transgenic rat model of AD, the present experiments were aimed at determining the sequence of appearance of Ab and hyperphosphorylated tau (p-tau) pathology in synaptic terminals.…”
mentioning
confidence: 99%
“…Growing evidence exists that native Aβ, which is produced during neuronal activity (Cirrito et al ., 2005), may subserve physiological functions (reviewed in Giuffrida et al ., 2010; Kepp, 2016). In particular, endogenous Aβ seems to be relevant for the control of synaptic activity and memory formation (Puzzo et al ., 2011; Piccini et al ., 2012), via the activation of α‐7‐nAChRs (Calabrese, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which memantine regulates amyloid metabolism is not clear. It has been shown that increased neuronal activity leads to increased APP production, a likely precursor to Ab plaque formation (Cirrito et al, 2005). Thus, blockade of NMDA receptors by memantine could reduce neuronal activity and subsequently lower APP production.…”
Section: Discussionmentioning
confidence: 99%